Exploring Cloud-Based Materials as Authentic and Relevant Models for Teaching Lexicogrammar - Barans I. Palangan (English Education Department - Universitas Nasional Karangturi, 2021)
Teaching English, particularly teaching its lexicogrammatical concepts, has been a challenging problem for teachers in Indonesia during this pandemic. The 'new normal' era has forced teachers to find cloud-based lexicogrammar materials for modeling activities in their online classes. These lexicogrammar materials are fortunately abundant on the internet, yet teachers, who are not English native speakers, still must search for authentic and relevant models. The purpose of this research, therefore, is to explore and present authentic and relevant cloud-based English lexicogrammar materials that can be good models for Indonesian teachers. In this exploratory study, both online and literature types of research were conducted to answer the formulated hypothetical question,